2002
DOI: 10.1002/job.155
|View full text |Cite
|
Sign up to set email alerts
|

The process of burnout in white‐collar and blue‐collar jobs: eight‐year prospective study of exhaustion

Abstract: SummaryThis study tested three contrasting theories about the sequential process of the three dimensions of burnout (i.e., exhaustion, cynicism and professional efficacy) as measured by the Maslach Burnout Inventory-General Survey (MBI-GS). The causal order of the burnout components was investigated by including job stressors as antecedents of burnout in structural equation models (LISREL). The predictive effect of exhaustion on burnout dimensions eight years later was also investigated. The longitudinal model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
139
1
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(168 citation statements)
references
References 32 publications
12
139
1
7
Order By: Relevance
“…Regarding level of occupational well-being, prior longitudinal research has reported fairly high values of vigour and fairly low or moderate values of exhaustion in terms of whole sample means (e.g. Dunford, Shipp, Boss, Angermeier, & Boss, 2012;Schaufeli et al, 2009;Toppinen-Tanner, Kalimo, & Mutanen, 2002). On the basis of these results, a large proportion of the sample was expected to display good occupational well-being.…”
Section: The Present Studymentioning
confidence: 92%
“…Regarding level of occupational well-being, prior longitudinal research has reported fairly high values of vigour and fairly low or moderate values of exhaustion in terms of whole sample means (e.g. Dunford, Shipp, Boss, Angermeier, & Boss, 2012;Schaufeli et al, 2009;Toppinen-Tanner, Kalimo, & Mutanen, 2002). On the basis of these results, a large proportion of the sample was expected to display good occupational well-being.…”
Section: The Present Studymentioning
confidence: 92%
“…Nevertheless, only rarely articles focus on this potential moderator effect. Studies which did distinguish between occupational groups in their analyses of the effects of job characteristics on employee outcomes are the studies of Schreurs et al (2011), Tsaur, Yen & Yang (2010 and Toppinen-Tanner, Kalimo & Mutanen (2002). Schreurs et al (2011) distinguished between white-and blue-collar employees in the relation between the job design and early retirement.…”
Section: Occupational Groups Mattermentioning
confidence: 99%
“…Tsaur, Yen & Yang (2010) researched the job design -employee creativity relationship in the travel agency industry and distinguished between four distinct employee categories. ToppinenTanner, Kalimo & Mutanen (2002) studied the effect of job stressors on burn-out and compared white with blue collar employee. All these studies concluded the relation between job design and employee outcomes depends on the occupational groups, but most studies only found small differences.…”
Section: Occupational Groups Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…Its severe individual (e.g., reduced physical health) and organizational consequences (e.g., reduced job performance, increased turnover and associated costs) have been convincingly demonstrated by a plethora of research (e.g., Burke, Greenglass, & Schwarzer, 1996;Toppinen-Tanner, Kalimo, & Mutanen, 2002).…”
Section: Introductionmentioning
confidence: 99%